Enrique Martínez Celaya : collected writings and interviews, 2010-2017 - Martínez Celaya, Enrique, 1964- (University of Nebraska Press, 2020)
"This collection, spanning nearly a decade of artistic activity, features selections of writings that trace the intellectual influences and track the development of one of the more formidable and productive minds in the contemporary art world"--